Study on Impact Resistance of C/SiC Ceramic Matrix Composites for Thermal Protection of the Aerospace Vehicle. (23rd August 2021) - Lin, Ye; Liu, Bin
Abstract : This paper evaluates the impact damage tolerance of ceramic matrix composites and contrasts their tensile and compression strengths under impact and nonimpact conditions. The representative C/SiC composites from PIP are examined under the dropped tip system. In this paper, the surface impact test of C/SiC composites is carried out. By testing a series of specimens of various impact energies, the tensile and compression properties after impact are studied. Meanwhile, by comparing the changes of the specimens after impact and nonimpact, the fracture process, fracture modes, and residual strength are investigated. The results indicate that the residual tensile strength after impact reduces greatly, compared with the nonimpact material, by about 25%–45%, while the compression strength reduces slightly. The residual strength of tension and compression illustrates that low-energy impact effect on the structural integrity must be given priority in the thermal protection structure design of astronautics and aeronautics.